Generativity affects fear of death through ego integrity in German, Czech, and Cameroonian older adults. (July 2018) - Busch, Holger; Hofer, Jan; Poláčková Šolcová, Iva; Tavel, Peter
Highlights: Tests how generativity and ego integrity relate to fear of death in the elderly. Generativity is indirectly related to reduced fear of death through ego integrity. Finds an indirect effect in samples from Germany, the Czech Republic, and Cameroon. Abstract: This cross-cultural study examined a potential direct effect of generativity and indirect effect through ego integrity on fear of death. In sum, 617 adults aged 60–86 from Germany, the Czech Republic, and Cameroon provided self-report information on their generative concern, ego integrity, and fear of death. Whereas it had no direct effect, generativity had an indirect effect on fear of death: It was associated with increased ego integrity which, in turn, was associated with reduced fear of death. This pattern was verified for the three cultural groups via structural equation modeling. Results suggest that generativity is not sufficient in coming to terms with one's mortality. Instead, generativity contributes to ego integrity which then helps to face death relatively unafraid.